Physical function improvements and relief from fatigue and pain are associated with increased productivity at work and at home in rheumatoid arthritis patients treated with certolizumab pegol. - Hazes, J; Taylor, P; Strand, V; Purcaru, O; Coteur, G; Mease, P (2010)
OBJECTIVES: To evaluate the association between improvements in physical function, fatigue and pain and improvements in productivity at work and at home in patients treated with certolizumab pegol (CZP) in combination with MTX. METHODS: Physical function, fatigue and pain were assessed in two CZP clinical trials (Rheumatoid Arthritis PreventIon of structural Damage 1 and 2) using the HAQ-Disability Index (HAQ-DI), Fatigue Assessment Scale (FAS) and Patient Assessment of Pain, with minimal clinically important differences (MCIDs) defined as ≥ 0.22, ≥ 1 and ≥ 10 points, respectively. Work and home productivity were evaluated using the RA-specific Work Productivity Survey (WPS-RA). The odds of achieving an HAQ-DI, FAS or pain 'response' at Week 12, defined as improvements ≥ MCID, were compared between CZP and control groups. Improvements in productivity at Week 12 were compared between CZP-treated HAQ-DI, FAS or pain responders and non-responders. RESULTS: The odds of achieving improvements ≥ MCID were five times higher for pain, and two to three times higher for physical function and fatigue, in patients receiving CZP vs control. Per month, responders reported significantly greater improvements in productivity at work and reduced interference of RA with their work productivity than non-responders. Responders also reported significantly greater improvements in productivity at home and participation in family, social and leisure activities. CONCLUSIONS: This study demonstrated a clear association between patient-reported improvements in physical function, fatigue and pain, and improvements in productivity both at work and home.